Efficiency of Application of Selection of Educational and Training Methods of Physical Preparation for Paralympic Athletes - Zulfiya Palibayeva (International Journal of Medical Toxicology and Legal Medicine, 2024)
The aim of the study is to compare the effectiveness of using educational and training methods in the field of adaptive physical education and Paralympic sports in the practice of training handball players. Particular attention is paid to the results of using the set of exercises developed by the author based on the methodology of psychophysical training (based on the use of the psycho-emotional factor) in combination with the use of physical exercises from a wide range of classical and non-traditional training systems.